Postintensive Care Syndrome in Survivors of Critical Illness Related to Coronavirus Disease 2019: Cohort Study From a New York City Critical Care Recovery Clinic*. Issue 9 (17th March 2021) - Martillo, Miguel A.; Dangayach, Neha S.; Tabacof, Laura; Spielman, Lisa A.; Dams-O'Connor, Kristen; Chan, Christy C.; Kohli-Seth, Roopa; Cortes, Mar; Escalon, Miguel X.
Abstract : OBJECTIVE: Determine the characteristics of postintensive care syndrome in the cognitive, physical, and psychiatric domains in coronavirus disease 2019 ICU survivors. DESIGN: Single-center descriptive cohort study from April 21, to July 7, 2020. SETTING: Critical care recovery clinic at The Mount Sinai Hospital in New York City. PATIENTS: Adults who had critical illness due to coronavirus disease 2019 requiring an ICU stay of 7 days or more and who agreed to a telehealth follow-up in the critical care recovery clinic 1-month post hospital discharge. INTERVENTIONS: None. MEASURES AND MAIN RESULTS: Patient-reported outcome measures assessing physical and psychiatric domains were collected electronically, a cognitive test was performed by a clinician, and clinical data were obtained through electronic medical records. Outcome measures assessed postintensive care syndrome symptoms in the physical (Modified Rankin Scale, Dalhousie Clinical Frailty Scale, Neuro-Quality of Life Upper Extremity and Lower Extremity Function, Neuro-Quality of Life Fatigue), psychiatric (Insomnia Severity Scale; Patient Health Questionnaire-9; and Posttraumatic Stress Disorder Checklist for Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition), and cognitive (Telephone Montreal Cognitive Assessment) domains. The 3-Level Version of Euro-QoL-5D was used to assess the physical and psychiatric domains. A diagnosis of postintensive care syndrome was made in cases with evidence of impairment in at least one postintensive care syndrome domain. We included 45 patients with a mean (sd ) age of 54 (13) years, and 73% were male. Ninety-one percent of coronavirus disease 2019 ICU survivors fit diagnostic criteria for postintensive care syndrome. 86.7 % had impairments in the physical domain, 22 (48%) reported impairments in the psychiatric domain, and four (8%) had impairments on cognitive screening. We found that 58% had some degree of mobility impairment. In the psychiatric domain, 38% exhibited at least mild depression, and 18 % moderate to severe depression. Eighteen percent presented Posttraumatic Stress Disorder Checklist for Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, scores suggestive of posttraumatic stress syndrome diagnosis. In the Telephone Montreal Cognitive Assessment, 9% had impaired cognition. CONCLUSIONS: Survivors of critical illness related to coronavirus disease 2019 are at high risk of developing postintensive care syndrome. These findings highlight the importance of planning for appropriate post-ICU care to diagnose and treat this population.